The feasibility of using local general practice data to estimate the prevalence of childhood disabling conditions. Issue 1 (19th June 2012) - Lingam, R.; Ellis, M.; Naqvi, H.; Mytton, J.
Abstract Aims This study aimed to assess the feasibility of using general practice data to estimate the prevalence of potentially disabling conditions in young people aged 0–18 years. Background There are limited data that estimate the prevalence of disabling conditions in children and young people and are suitable to inform service planning. This has been highlighted by several government documents and parent groups. The current study analysed anonymized data from 5 general practices in Bristol, UK (n = 10 756 children and young people aged 0–18 years). A comprehensive Read Code list was created to identify children and young people with potentially disabling conditions and the severity of conditions was compared with General Practitioner completed free text within the computerized system. Results Across these practices an average 4.9% (95% confidence intervals 4.5–5.3) of children and young people had a significant physical or mental difficulty that could impact on their daily living. The most common disabling conditions in our sample were in the ICF category of mental function 36% (including general and specific developmental delays and mental health diagnoses). Conclusion This study suggests that routinely collected data may provide much needed robust information to inform service provision for some of the most vulnerable children and young people in our communities. It also highlights the need for improved data systems for disability services.